Evaluation of bridge-scour research abutment and contraction scour processes and prediction - Sturm, Terry W. (National Cooperative Highway Research Program, Transportation Research Board of the National Academies, 2011)
This report reviews the present state of knowledge regarding bridge-abutment scour and the veracity of the leading methods currently used for estimating design scour depth.
Title from PDF title page (viewed on December 16, 2011).
"Contractor's final report for NCHRP project 24-27(02), submitted September 2011."
Keywords: Scour at bridges -- United States.; Bridges -- United States -- Abutments.; Transportation -- United States -- Mathematical models.; Transportation -- Research -- United States.; United States.; elektronické knihy; electronic books